Treatment of Displaced Olecranon Fractures: A Systematic Review - Rantalaiho I.; Miikkulainen A.; Laaksonen I.; Äärimaa V.; Laimi K. (SAGE Publications Inc., 2022)
Background and Aims:
The incidence of olecranon fractures is rising. Displaced fractures are usually operated either by tension band wiring or plate fixation. The aim of this review is to evaluate the best current evidence on the management of displaced olecranon fractures.
Materials and Methods:
Randomized controlled trials were systematically gathered in May 2018 from CENTRAL, MEDLINE, Embase, CINAHL, Scopus, and PEDro databases. The methodological quality of articles was assessed according to the Cochrane Collaboration’s domain-based framework. Prospero database registration number: CRD42018096650.
Results:
Of 1518 identified records, finally, 5 were relevant. Four trials were found on tension band wiring: two compared tension band wiring with plate fixation (n = 108), one compared plate fixation with an olecranon memory connector (n = 40), and one trial compared tension band wiring with a modified tension band wiring called Cable Pin System (n = 62). In addition, one trial compared operative and conservative treatment in elderly (n = 19). The risk of bias was considered low in two and high in three of the trials. The follow-up time was 5–36 months, and outcome measures varied from patient-rated and physician-rated measures to radiological outcomes. In the analysis, there was no difference between tension band wiring and plate fixation. The data were insufficient for further quantitative analysis.
Conclusion:
No differences were found in clinical or patient-rated outcome measures between the two most frequent fixation methods (tension band wiring and plate fixation) of displaced olecranon fractures. Current data are not sufficient to evaluate other treatment methods; however, conservative treatment might serve as an option for selected patients in the elderly population.